2014
DOI: 10.1007/s00406-014-0491-y
|View full text |Cite
|
Sign up to set email alerts
|

Increased neural activity during overt and continuous semantic verbal fluency in major depression: mainly a failure to deactivate

Abstract: Major depression is associated with impairments in semantic verbal fluency (VF). However, the neural correlates underlying dysfunctional cognitive processing in depressed subjects during the production of semantic category members still remain unclear. In the current study, an overt and continuous semantic VF paradigm was used to examine these mechanisms in a representative sample of 33 patients diagnosed with a current episode of unipolar depression and 33 statistically matched healthy controls. Subjects arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 132 publications
1
15
0
Order By: Relevance
“…This aberrant, symptom-related hyperactivity of the precuneus in MDD patients has not been reported in previous studies using the PVF [12] and indicates that the SVF has an advantage for investigating an MDD patient's neuropathology. In addition, the previous study using the SVF [15] also demonstrated decreased suppression in brain regions related to task-irrelevant self-referential thoughts in MDD patients, and this is in line with the present results.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This aberrant, symptom-related hyperactivity of the precuneus in MDD patients has not been reported in previous studies using the PVF [12] and indicates that the SVF has an advantage for investigating an MDD patient's neuropathology. In addition, the previous study using the SVF [15] also demonstrated decreased suppression in brain regions related to task-irrelevant self-referential thoughts in MDD patients, and this is in line with the present results.…”
Section: Discussionsupporting
confidence: 82%
“…The results of these studies suggest that the PVF can reveal MDD patients' impaired executive function related to attenuated left prefrontal cortex (PFC) activity. However, to our knowledge, there is only 1 fMRI study [15] that compares neural activation during SVF between MDD patients and healthy control (HC) subjects directly. They demonstrated aberrant brain activation during SVF in patients with MDD [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most common patterns of cognitive impairment observed in these conditions is executive dysfunction, which is defined as an alteration in cognitive abilities such as inhibitory control, working memory, cognitive flexibility, planning, and problem solving, collectively known as the executive functions (EFs) (Diamond, 2013). Consistent impairments in related functions such as divided attention and verbal fluency have also been identified in both BD (Allin et al, 2010;Păunescu & Micluţia, 2015) and MDD (Backes et al, 2014), with significant implications for psychosocial and occupational functioning (Evans et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In an fMRI study, Backes et al [8] examined brain activation during articulation of words in response to semantic category cues. Compared to healthy controls, patients with unipolar depression showed poorer task performance and after correction for task performance, patients displayed reduced task-related deactivation in the right parahippocampal gyrus, right fusiform gyrus and right supplemental motor area.…”
mentioning
confidence: 99%